The Influence of Students’ Views, Attitudes, and Curiosity Characters on the Physical Education Learning Outcomes of Middle School Students - Ugi Nugraha; Retni Sulistiyoning Budiarti; Ely Yuliawan (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to see how the influence of perception, attitude, and curiosity character instruments on learning outcomes used in junior high school students in Tebo in the subject of Physical Education. Methodology: Quantitative analytical descriptive methods were used in this research. The research sample consisted of junior high school students in Tebo who were involved in Physical Education learning. Main Findings: Data collection was carried out through students' perceptions, attitudes. and curiosity characters towards student learning outcomes in this subject at Junior high school 2 Tebo with 40% in the sufficient category. In addition, students' perceptions, attitudes, and curiosity characters towards student learning outcomes in this subject at Junior high school 16 Tebo tend to be positive with 36% in the sufficient category which can have a positive impact on student activity in learning activities and physical activities. Novelty/Originality of this study: The novelty of this study lies in the exploration of the relationship between students' perspectives, attitudes, and curiosity characters towards Physical Education learning with their learning outcomes at the junior high school level.